LEKSIKON SEBAGAI SARANA PEMBUAT KLASIFIKASI: KAJIAN AWK DALAM BERITA KONFLIK PERBATASAN INDONESIA-MALAYSIA - Dwi Harjanti, Fransisca (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This writing research the using of lexicon as the power mean to do marginalization practice to other group. One of lexicon role in in news language is classification made. With classification, we can see the forms of lexicon that showed pro and contra attitude The data is taken from press mass media that is used as the source of this research are Kompas, Jawa Pos, Republika, and Media Indonesia. On this writing is showed that lexicon as a mean which made classification can be difference as a pro and contra. Lexicon that showed contra attitude is used to decomposition to other group, while the attitude is used to provide the interest of the other group and put their group it self into a corner. Some is lexicon which is used to make classification, some of them is used to discourse fight.